ANALISIS EFEKTIVITAS BIAYA OMEPRAZOLE DAN RANITIDIN PADA PASIEN DISPEPSIA DI INSTALASI RAWAT INAP RSUD UNDATA PALU - Ririen Hardani; Nurul Ambianti; Rudi Safarudin; Tri Atainah Syafaah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
The prevalence rate of dyspepsia continues to increase, with cases of recurrence occurring in patients not only adding to the physical and psychological burden of patients, but can also pose an economic burden on both patients and the health system. This study aims to determine the cost of therapy in dyspepsia patients based on the ACER value. This study is a descriptive study, data obtained from medical records and financial data of dyspepsia patients at Undata Hospital, Palu. Data analysis was done descriptively using Microsoft excel and statistically using Kruskal wallis test, Chi-square and independent T-test. The results of the study based on the Kruskal wallis test obtained a p-value of 0.002 which indicates that there is a significant effect of secondary diagnosis on direct medical costs of dyspepsia patients, and the cost effectiveness of therapy based on the ACER value of omeprazole of Rp 35,965 and the ACER value of ranitidine of Rp 28,965. The conclusion of this study is that ranitidine is more cost effective than omeprazole in dyspeptic patients at the inpatient installation of RSUD Undata Palu.